EXPERIMENTAL STUDY ON THE EFFECT OF AIR-DRYING ON DURABILITY OF EMBALMED HUMAN CADAVERS (Iraqi Journal of Medical Sciences, 2016)
Background:The embalmed human cadavers used for teaching anatomy in the medical colleges could be preserved for a very long time, the crucial factors for acheivement of this prolonged preservation was not fully discussed.Objectives:This is an experimental study to evaluate the veracity of using paraffin sectioning feasibility as a test for the degree of damage in the embalmed cadaveric tissue affected by recurrent and prolonged air drying in anatomy laboratories.Methods: Routine paraffin sections were done for tissues obtained from cadaveric organs exposed to recurrent and prolonged air drying and tissues from cadaveric organs preserved most of the time in a hydrated condition.Results:The results of this study showed unblemished paraffin sectioning of the emblamed cadaveric tissue preserved with good hydration. The cadaveric tissues exposed to reccurent air drying could not be sectioned properly, the sectioned tissues were hard and brittled.Conlcusion: The experts dealing with the embalmed cadavers evidently necessitude maintancance of cadaveric hydration as a requisite to prolong durability of the demonstrative details in the dissected cadavers. Accordingly; the comparably more proper paraffin sectioning of the well hydrated cadaveric tissue may be considered as a sign of more durable embalmed cadaveric organs.Keywords :cadaver, paraffin, anatomy, fixation, formalin.
Keywords: cadaver; paraffin; anatomy; fixation; formalin